Phonological Awareness on Students’ Pronunciation Accuracy in English - Jannicolas Elsamnuari Sihombing; Laura Sesilia Sihaloho; Sry Ucy Uly Sianipar; Bloner Sinurat (Yayasan Bayt Shufiya Nusantara, 2025)
This study aims to examine the influence of phonological awareness on the pronunciation accuracy of non-native English learners, with a specific focus on both segmental and suprasegmental features. Employing a library reasearch design. The investigation explored common pronunciation challenges related to vowel sounds particularly pure vowels and diphthongs as well as word stress and rhythm patterns. The findings indicate that students frequently struggle with distinguishing vowel length, producing diphthong glides, and placing stress on the correct syllables. These pronunciation difficulties are largely influenced by the phonological system of their first language, Bahasa Indonesia, which does not contain equivalent phonemic contrasts or prosodic features. As a result, these challenges negatively affect the intelligibility and fluency of their spoken English. The study supports the theory of interlanguage phonology, highlighting how learners construct an intermediate sound system based on both L1 and L2 influences.